2020
DOI: 10.1016/j.jiac.2019.10.013
|View full text |Cite
|
Sign up to set email alerts
|

WQ-3810 inhibits DNA gyrase activity in ofloxacin-resistant Mycobacterium leprae

Abstract: BackgroundMycobacterium leprae causes leprosy and ofloxacin is used to control this bacterium. However, specific amino acid substitutions in DNA gyrases of M. leprae interferes with the effect of ofloxacin. Methodology/principal findingsHere we tested the inhibitory effect of WQ-3810 on DNA gyrases in M. leprae, using recombinant gyrases. We theorized that WQ-3810 and DNA gyrases interacted, which was tested in silico.Compared with control drugs like ofloxacin, WQ-3810 showed a better inhibitory effect on oflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…12,20 In the previous study, to elucidate the potential of WQ-3810 as a drug for leprosy, its inhibitory effect against DNA gyrases of M. leprae was assessed instead of measuring the minimum inhibitory concentration. 14 This approach was used because M. leprae is yet to be cultured in artificial media. The IC 50 , calculated using a supercoiling inhibitory assay, was used as a reliable criterion for the therapeutic potency of fluoroquinolones against M. leprae.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…12,20 In the previous study, to elucidate the potential of WQ-3810 as a drug for leprosy, its inhibitory effect against DNA gyrases of M. leprae was assessed instead of measuring the minimum inhibitory concentration. 14 This approach was used because M. leprae is yet to be cultured in artificial media. The IC 50 , calculated using a supercoiling inhibitory assay, was used as a reliable criterion for the therapeutic potency of fluoroquinolones against M. leprae.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent in silico study, WQ-3810 showed an additional association with GyrB that may enhance its inhibitory effect on quinoloneresistant DNA gyrases bearing GyrA amino acid substitutions. 14 For a better understanding of this assumption, an additional comparison with WQ compounds having different R1 and R8 groups was deemed necessary.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations